M-Health terhadap Kepatuhan Pengobatan pada Pasien Hipertensi - Noviyanti, Merry; Triharini, Mira; Ulfiana, Elida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide an opportunity for hypertensive patients to receive education and information related to hypertension and medication from health workers via their cell phones. The method used to search for articles relevant to the study in September-October 2023 was carried out using three stages, namely: planning, conducting, and reporting. The results obtained show that as many as 10 international articles analyzed in this paper have passed screening according to the inclusion and exclusion criteria. The journals or articles reviewed include the year of publication, database, research design, and location. In conclusion, the use of M-Health has been proven to be effective in making sufferers more compliant with every treatment carried out, especially when treatment is hampered by geographical problems. This M-Health innovation can help the process of effective management and control of hypertension. Keywords: M-Health, innovation, medication adherence, hypertension